Tingkat Kepuasan Konsumen terhadap Kualitas Layanan pada Waserda Yaponpes Dayama Desa Jerowaru Kabupaten Lombok Timur - Muhammad Nashruddin (PALAPA, 2017)
The study aims to determine the level of customersatisfaction with service quality Waserda Ponpes Dayama Jerowaru Village. The method used in this research is the method of Important Performance Analisys (IPA) with the presentation of data descriptively. The number of samples taken as many as 30 respondents taken by random sampling. Based on the calculation results obtained 936 customer satisfaction score score that means consumers feel quite satisfied. Based on the analysis using Performance Analisys (IPA) method, it is known that some important attributes that have been stated have contributed to give satisfaction to the consumer that is attribute number 1 (wide parking area) and number 10 (strategic location)